The hand motor hotspot for seed-based functional connectivity of hand motor networks at rest - Bonzano, Laura; Bortoletto, Marta; Zazio, Agnese; Iester, Costanza; Stango, Antonietta; Gasparotti, Roberto; Miniussi, Carlo; Bove, Marco (Frontiers in Neuroscience, 2022)
In the seed-based method for studying functional connectivity (FC), seed selection is relevant. Here, we propose a new methodological approach for resting-state FC analysis of hand motor networks using the individual hand motor hotspot (hMHS) as seed. Nineteen right-handed healthy volunteers underwent a transcranial magnetic stimulation (TMS) session and resting-state fMRI. For each subject, the hMHS in both hemispheres was identified by TMS with contralateral abductor pollicis brevis muscle as target, as the site eliciting the highest and most reliable motor evoked potentials. Seed regions were built on the coordinates on the cortex corresponding to the individual left and right hMHS. For comparison, the left and right Brodmann’s area 4 (BA4) masks extracted from a standard atlas were used as seed. The left and right hMHS showed FC patterns at rest mainly including sensorimotor regions, with a bilateral connectivity only for the left hMHS. The statistical contrast BA4>hMHS, for both hemispheres, showed different extension and lateralization of the functionally connected cortical regions. On the contrary, no voxels survived the opposite contrast (hMHS>BA4). This suggests that the detection of individual hand motor seeds by TMS allows to identify functionally connected motor networks that are more specific with respect to those obtained starting from the a priori atlas-based identification of the primary motor cortex.